1999
DOI: 10.1002/(sici)1097-0290(19990120)62:2<235::aid-bit14>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Engineered isoprenoid pathway enhances astaxanthin production inEscherichia coli

Abstract: The isoprenoid pathway is a versatile biosynthetic network leading to over 23,000 compounds. Similar to other biosynthetic pathways, the production of isoprenoids in microorganisms is controlled by the supply of precursors, among other factors. To engineer a host that has the capability to supply geranylgeranyl diphosphate (GGPP), a common precursor of isoprenoids, we cloned and overexpressed isopentenyl diphosphate (IPP) isomerase (encoded by idi) from Escherichia coli and GGPP synthase (encoded by gps) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 39 publications
5
92
0
1
Order By: Relevance
“…Subsequently, the isopentenyl pyrophosphate isomerase (IPI) catalyzes the isomerization of IPP to dimethylallyl diphosphate (Lichtenthaler 1999). Introduction of a heterologous IPI gene in Escherichia coli enhanced the accumulation of carotenoids, supporting a role of IPI in regulating carotenoid biosynthesis (Kajiwara et al 1997, Wang et al 1999. Two cDNAs of IPI, IPI1 and IPI2 have been cloned and characterized in H. pluvialis (Sun et al 1998).…”
Section: Biosynthesis Of Astaxanthin In Haematococcus Pluvialismentioning
confidence: 93%
“…Subsequently, the isopentenyl pyrophosphate isomerase (IPI) catalyzes the isomerization of IPP to dimethylallyl diphosphate (Lichtenthaler 1999). Introduction of a heterologous IPI gene in Escherichia coli enhanced the accumulation of carotenoids, supporting a role of IPI in regulating carotenoid biosynthesis (Kajiwara et al 1997, Wang et al 1999. Two cDNAs of IPI, IPI1 and IPI2 have been cloned and characterized in H. pluvialis (Sun et al 1998).…”
Section: Biosynthesis Of Astaxanthin In Haematococcus Pluvialismentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]Isopentenyl diphosphate (IPP) and [1-3 H]GGPP were purchased from Amersham Biosciences. All other chemicals were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction product was hydrolyzed with acid phosphatase and analyzed by HPLC, using a YMC-Pack ODS-A column (4.6 ϫ 250 mm, YMC) eluted with methanol/2-propanol (7:3). The proportion of 3 H and 14 C radioactivities that co-eluted with the peak of the new product was measured using a ramona Star radio-HPLC analyzer (Raytest).…”
Section: Fig 2 Biosynthetic Pathway Of Archaeal Membrane Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, overexpression of DXS or GGPPS in combination with a carotenoid cluster significantly enhanced carotenoids produced in an E. coli bacterial platform (Wang et al, 1999;Matthews and Wurtzel, 2000). Similar examples in other plants have shown that overexpression of genes for certain upstream precursor pathway enzymes (DXS, DXR, or HDR) plus a downstream pathway enzyme forced pathway flux to the downstream pathway (BotellaPavia et al, 2004;Carretero-Paulet et al, 2006;MunozBertomeu et al, 2006).…”
Section: Upstream Isoprenoid Biosynthesis Controls Downstream Endospementioning
confidence: 99%